Sensitivity analysis of a direct problem solution to kinetic parameters changes in a given range - MEDVEDEVA, O.A; MUSTAFINA, S.I; MUSTAFINA, S.A; SMIRNOV, D.Y; YASHIN, D.D (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe paper shows a technique of researching the direct kinetic problem sensitivity to the variation of the kinetic parameters within a given range. This technique is based on the use of the computing device of the interval analysis. The direct problem solution in the conditions of kinetic parameter uncertainty was received by the interval method of the solution of a Cauchy problem for differential equations system. The interval characteristics received during this method application were used for the research of reagents and product concentration sensitivity about kinetic parameters of a mathematical model of industrially important reaction. RESUMENEl artículo muestra una técnica de investigación de la sensibilidad del problema cinético directo a la variación de los parámetros cinéticos. Esta técnica se basa en el uso del dispositivo informático del análisis de intervalos. La solución del problema directo en las condiciones de incertidumbre de los parámetros cinéticos se recibió mediante el método de solución de intervalo de un problema de Cauchy para el sistema de ecuaciones diferenciales. Las características de intervalo recibidas durante la aplicación de este método se usaron para la investigación de reactivos y sensibilidad de concentración de productos en relación con reacciones de importancia industrial.